STUDI KEKUATAN MENARA BTS (BASE TRANSCEIVER STATION) PADA MENARA SST TINGGI 72M TIPE GREENFILED - Novia Santi Marsia; Chandra Afriade Siregar (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
The development of communication technology in Indonesia has grown quite rapidly. The increasing needs of the community for telecommunications make cellular operators continue to improve services. To increase network capacity can be done by adding devices on telecommunication towers. The addition of devices on telecommunication towers brings consequences in the form of increased loads that must be carried by the telecommunication tower. The stability check of a 4-foot SST-type BTS tower with a height of 72m refers to the EIA/TIA-222-G standard and uses the MS Tower V6 program. The check includes several things, namely: the stress ratio that occurs in the tower element, tower sway, tower torsion, tower shift, and the reaction of the support that occurs. If the addition of devices in the telecommunication tower is still within the capacity limit of the tower, the addition of devices is not a problem. If one of the above criteria is passed even though the other criteria are safe, the tower structure is considered unsafe and must be recalculated. The results of the analysis when the tower was given an additional antenna load found that the tower did not meet 1 limit condition because the stress ratio exceeded the standard, which was 1.212 (>1). So it needs to be reinforced at the foot of the tower using the L60x60x6 profile. From the results of reinforcement at the foot of the tower, it was found that the stress ratio value < 1 with a value of 0,938 and the sway value < 0,5, which is worth 0.2303, so the tower has met the requirements.